Back Cover: Novel Strategy to Drive the Intracellular Uptake of Lipid Nanoparticles for Photodynamic Therapy (Angew. Chem. Int. Ed. 16/2023). Issue 16 (15th March 2023) - Ho, Tiffany; Guidolin, Keegan; Makky, Ali; Valic, Michael; Ding, Lili; Bu, Jiachuan; Zheng, Mark; Cheng, Miffy H. Y.; Yau, Jeremy; Chen, Juan; Zheng, Gang
Abstract : The superior efficacy of aminopolycarboxylic acid conjugated lipid nanoparticles over standard liposomal nanoparticles is described by Juan Chen, Gang Zheng et al. in their Research Article (e202218218) . EDTA–lipid based nanoparticles fluidize the cell membrane in a detergent‐like manner and improve delivery to the cell by 25‐fold. This novel nanoparticle design feature can be deployed across lipid nanoparticles to accelerate cancer nanomedicine drug delivery.